Development of novel photocatalytic overall water splitting systems at elevated temperatures for efficient hydrogen evolution - Li, Y (2021)
Environmental and energy issues have become one of the most important issues that human beings are facing, and carbon neutrality is a communal target worldwide nowadays. With the strong international incentives to decarbonise our fuels and chemicals, the solar-light-driven photocatalytic overall water splitting (POWS) reaction provides a promising and renewable way to store and utilise the abundant solar energy in the form of hydrogen which is the cleanest chemical fuel for mankind. Numerous materials and catalytic systems have been developed for more effective solar energy conversion, however, the performance achieved so far is still unsatisfactory.